2021
DOI: 10.1159/000518090
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Antibiotics during Immune Checkpoint Inhibitor Treatment Is Associated with Lower Survival in Hepatocellular Carcinoma

Abstract: <b><i>Background:</i></b> Recent studies suggested that use of antibiotics may interfere with treatment responses to immune checkpoint inhibitors (ICIs). We determined whether concurrent use of antibiotics during ICI therapy was associated with adverse outcomes in patients with advanced hepatocellular carcinoma (HCC). <b><i>Methods:</i></b> This is a territory-wide retrospective cohort study including all advanced HCC patients who received ICIs (nivolumab, pembro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…Studies retrieved and characteristics 467 eligible records were screened for their titles and abstracts to check for their eligibility. After a detailed analysis of 14 full-text records, we found that six studies met the inclusion criteria (17,18,(20)(21)(22)(23). The articles by Ren et al (24) and Jun et al (25) were excluded from the meta-analysis due to insufficient data and duplicate publication, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Studies retrieved and characteristics 467 eligible records were screened for their titles and abstracts to check for their eligibility. After a detailed analysis of 14 full-text records, we found that six studies met the inclusion criteria (17,18,(20)(21)(22)(23). The articles by Ren et al (24) and Jun et al (25) were excluded from the meta-analysis due to insufficient data and duplicate publication, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One of the limitations of the current study is the definition of antibiotic use, including the duration of exposure and the time interval between last antibiotic use and vaccination. We used an arbitrary cutoff of ever use of any antibiotics within six months before vaccination [ 21 ], as antibiotic-induced gut microbiota perturbation took at least six months to recover [ 9 ]. Due to the relatively small number of antibiotic users ( n = 29), any stratified analysis according to duration of antibiotic use and the time interval from last antibiotic use will likely suffer from underpower.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of interest was pre-vaccination antibiotic use, defined as ever use of any antibiotics within six months before vaccination [ 21 ]. The six-month cut-off was used because antibiotic-induced gut microbiota perturbation took months to recover [ 9 ].…”
Section: Exposure Of Interest and Covariatesmentioning
confidence: 99%
“…The humanized monoclonal antibodies target inhibitory receptors to provoke an antitumor immune response and modulate T-cell activation by interrupting the delivery of inhibitory signals ( 73 ). A retrospective cohort study investigated the impacts of antibiotics on the clinical trial results of ICIs for treating patients with HCC ( 74 ). Antibiotics against anaerobes were linked with a higher risk of HCC-related death during ICI therapy when compared with antibiotics against aerobes.…”
Section: Antibiotics In Hccmentioning
confidence: 99%